2011
DOI: 10.1177/0969733011408053
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and burden with ethical conflicts and burnout in nurses

Abstract: Many studies examine a stressors-professional burnout (PB) relation, but only few consider the role of ethical conflicts (ECs) in this context. The aim of this study was to characterize ECs' frequency and level of burden with them among nurses and to establish the relations between ECs' frequency, burden and PB. One hundred nurses participated in this study. ECs' frequency and burden were tested with an originally developed questionnaire. PB was examined with Maslach Burnout Inventory. Most frequent ECs concer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 26 publications
1
40
0
Order By: Relevance
“…Some of research revealed ethical conflicts in ICU nurses. Wlodarczyk and Lazarewicz found a positive relationship between professional burnout and frequency of ethical conflicts among nurses in Poland (18). In Spain, the findings showed high levels of exposure to ethical conflicts (8).…”
Section: Introductionmentioning
confidence: 99%
“…Some of research revealed ethical conflicts in ICU nurses. Wlodarczyk and Lazarewicz found a positive relationship between professional burnout and frequency of ethical conflicts among nurses in Poland (18). In Spain, the findings showed high levels of exposure to ethical conflicts (8).…”
Section: Introductionmentioning
confidence: 99%
“…This was reported as a major barrier to receiving and providing mutual support for fear of confessing to a weakness and further embarrassment. This aspect was also identified by Wlodarczyk and Lazarewicz (, p.859) who stated: ‘Confessing to own weaknesses is not taken well in the professional environment’. The current findings point to the importance of mutual peer and social support, although identified as not forthcoming for several participants, it was emphasised as an important element in reducing their perceived social isolation.…”
Section: Discussionmentioning
confidence: 77%
“…19 The ethical dimension when caring for dying children is of great importance to consider, since conflicts about moral issues can affect not only the individual HCW but also the whole organization. 41 When HCWs are absent during the moment of death, parents' experiences are negatively affected. 26 It is interesting that HCWs in this study were similarly affected with emptiness and emotional pain, when they were not present at the moment the child died.…”
Section: Discussionmentioning
confidence: 99%